1997
DOI: 10.1098/rspb.1997.0227
|View full text |Cite
|
Sign up to set email alerts
|

The transmission dynamics of antibiotic–resistant bacteria: the relationship between resistance in commensal organisms and antibiotic consumption

Abstract: We propose a mathematical model of the transmission dynamics of colonization by commensal bacteria within a human community subject to varying levels of antibiotic use designed to control morbidity induced by pathogenic strains of the normally commensal organisms. Colonization is assumed not to induce morbidity in the majority of cases, and antibiotic use is assumed to be related to the arrival and growth of pathogenic strains that give rise to infections including clinical symptoms of disease. In the absence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
122
0
5

Year Published

2000
2000
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(130 citation statements)
references
References 19 publications
(18 reference statements)
3
122
0
5
Order By: Relevance
“…This clear-cut dis- It has previously been observed that so long as antimicrobial resistant mutations are present in host, drug resistance will always emerge once a new drug is introduced (Austin et al, 1997;Rong et al, 2007). In our study, it was demonstrated that this depends in turn on the recovery rate and on the magnitude of the transmission parameters.…”
supporting
confidence: 50%
See 4 more Smart Citations
“…This clear-cut dis- It has previously been observed that so long as antimicrobial resistant mutations are present in host, drug resistance will always emerge once a new drug is introduced (Austin et al, 1997;Rong et al, 2007). In our study, it was demonstrated that this depends in turn on the recovery rate and on the magnitude of the transmission parameters.…”
supporting
confidence: 50%
“…However the models by Austin et al (1997) and Kavanagh et al (2005) assumed that the treatment effect was constant whereas in our model, a more realistic time-varying treatment effect was assumed. Our model can be adapted to study the transmission dynamics of a commensal bacteria such as E. coli as well as a zoonotic bacteria such as Salmonella in animals following the models proposed by Austin et al (1997) and Kavanagh et al (2005) respectively.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations